IDENTIFICATION OF POTENTIAL DRUG RELATED PROBLEMS OF IMPROPER DOSAGE AND ADVERSE DRUG REACTIONS CATEGORIES IN OSTEOARTHRITIS OUTPATIENTS IN RSUD JOMBANG 2016 - Muslim, Ayu Tria Nurjannah; Hakim, Abdul; Dianti, Meilina Ratna (Journal of Islamic Pharmacy, 2018)
Osteoarthritis is a chronic disorder of synovial joints, characterized by progressive softening and disintegration of cartilage in joints. This is the most common type of arthritis in Indonesia with prevalence about 23.6 to 31.3% and generally suffered by middle age patients. Drug therapy for treating osteoarthritis is NSAIDs, supplements and corticosteroids. The increasing number of available drugs, drug users and more complex drug regimens caused more side effect and potential drug interaction and lead to another problem, it is Drug Related Problems. The purpose of this study was to identify potential Drug Related Problem categories of improper dosage and Adverse Drug Reactions in osteoarthritis outpatient in RSUD Jombang during 2016. This research is a non-experimental descriptive study conducted retrospectively, carried out in March 2017 at RSUD Jombang. Research sample is 87 respondents of osteoarthritis outpatient which taken by systematic random sampling method. The data presented in percentage of improper dosage and Adverse Drug reactions potential case. The result found potential of improper dosage in respondent about 82,76% and Adverse Drug Reactions about 20,69%.